PENUGASAN GURU UNTUK MELAKSANAKAN TUGAS-TUGAS ADMINISTRASI SEKOLAH (Studi Deskriptif Kualitatif Di SD Negeri 205 Bengkulu Utara) - sugiyatno Sugiyatno; rohiat rohiat (UNIVERSITAS BENGKULU, 2020)
This research generally aims to improve the ability of teachers who was given the task of the principal performing the task of school administration. In particular, this study aims to described the teachers’s task who get the mandate to perform the school’s administration in elementary schools include: (1) the implementation of personnel administration (2) implementing financial administration. (3) the administration of school facilities and infrastructure. (4) implementing public relations administration with the community. (5) carry out administrative mailing and archiving. (6) implementing student administration. This study used descriptive qualitative method. The subjects of this study were principals, school operators and teachers. The techniques and stages of data collection in this study were Unstructured Interviews, Observation and Documentation Studies. The result of the research shows that the teacher can assist the administrative tasks of the school such as: (1) to carry out personnel administration (2) to carry out financial administration (3) to carry out administration of school facilities and infrastructure. (4) implementing public relations administration with the community (5) carry out administration of mailing and archiving. (6) carry out student administration.Finally based on the above results, the researcher suggested the assignment of teachers to carry out the task of school administration by the principal can meet the absence of primary school educators.